Trafficking of the cellulose synthase complex in developing xylem vessels. (24th May 2010) - Wightman, Raymond; Turner, Simon
Abstract : The potential for using cellulosic biomass as a source of fuel has renewed interest into how the large cellulose synthase complex deposits cellulose within the woody secondary walls of plants. This complex sits within the plasma membrane where it synthesizes numerous glucan chains which bond together to form the strong cellulose microfibril. The maintenance and guidance of the complex at the plasma membrane and its delivery to sites of secondary wall formation require the involvement of the cytoskeleton. In the present paper, we discuss the dynamics of the complex at the cell cortex and what is known about its assembly and trafficking.